Anaesthesia affects immune function and impact on long-term cancer prognosis: A review - Kisdyanti Yuniar Melissa; Suandika Made; Rahmawati Arni Nur (BIO Web of Conferences)
The effect of anaesthesia on the immune system has been the focus of research over the last decade, particularly in cancer patients. Anaesthetic procedures, which are essential in surgical management, can affect the body’s immune response through direct and indirect mechanisms. Anti-tumour immunity is compromised by local and systemic immunosuppression, which may ultimately contribute to tumor survival and the long-term prognosis of cancer patients. This article aims to identify and evaluate the evidence on the effects of anaesthesia-induced immunosuppression, to determine the mechanisms by which anaesthesia affects the immune system during surgery, and the implications for cancer proliferation, metastasis, and recurrence. In addition, this article also evaluates the type of anaesthesia and explores the relationship between immune modulation during anaesthesia and long-term survival. This article uses the literature review method with the PICO and JBI tools analysis approach of 15 journals found through database searches on PubMed, ScienceDirect, and EBSCO. The study population is cancer patients, and the research reviewed provides an overview of research into the biological pathways involved, the effects of immunosuppression associated with anaesthesia, and the potential for anaesthetic interventions to minimize the negative impact on cancer prognosis. The review showed a significant association between the type of anaesthesia and modulation of the immune system and its impact on long-term survival. Conclusions from the literature highlight the importance of the appropriate choice of anaesthetic to improve clinical outcomes and long-term survival in cancer patients.